Task-Based Language Teaching in Promoting Students’ Speaking Fluency - Indri Fitriani; Yanty Wirza (Jurnal Bahasa dan Sastra, 2018)
Abstract: This study is conducted to investigate the use of task-based language teaching in pro- moting students’ speaking fluency. The students are exposed to four different tasks: sequencing task, picture narration task, question and answer task, and problem-solving task. The partici- pants of the study were thirty-six tenth grade students in one of the senior high schools in Band- ung. From thirty-six students, six students were selected as the representatives whose speaking performance were analysed. The students’ speaking performance were audio recorded and were analysed by looking at several linguistic aspects, such as segmental errors, speech rate, and grammatical accuracy. The findings of the study revealed that task-based language teaching promotes students’ speaking fluency. The students’ speech production showed improvement in the rhythm, segmental, speech rate aspect. The students showed positive responses during the task-based implementation in terms of awareness of the different aspect of English pronuncia- tion. In addition, the students’ participation in communicating in English was increased based on the observation result in each meeting and students’ interview. The study recommends that the students need to be exposed and learn the different aspects of pronunciation to further im- prove their speaking performance.Keywords: fluency, speaking skill, task-based language teaching.Abstrak: Penelitian ini meneliti penggunaan pengajaran Bahasa Inggris berbasis tugas (task- based instruction) untuk meningkatkan keterampilan berbicara Bahasa Inggris siswa. Dalam penelitian ini, siswa diberi empat macam tugas (tasks): menyusun, narasi gambar, tanya-jawab, dan pemecahan masalah. Siswa yang terlibat sebagai partisipan dalam penelitian ini berjumlah tiga puluh enam siswa kelas sepuluh dari salah satu SMP di Bandung. Dari tiga puluh enam siswa ini, enam di antaranya diambil contoh ujaran-ujarannya untuk diteliti lebih jauh menge- nai irama, segmental. Data diambil dari observasi, interview, dan penilaian performa berbicara Bahasa Inggris. Penelitian ini menemukan bahwa pengajaran Bahasa Inggris berbasis tugas dapat meningkatkan kemampuan berbicara siswa terutama dalam hal irama, aspeck segmental dan kecepatan berbicara. Siswa juga menunjukan respon positif dari pelaksanaan pembelajaran berbasis tugas ini yang terlihat dari meningkatnya kesadaran akan berbagai aspek dari pen- gucapan Bahasa inggris. Lebih lanjut, motivasi dan partisipansi siswa juga meningkat dalam berbicara berbahasa Inggris berdasarkan observasi dan interview. Penelitian ini merekomen- dasikan supaya siswa terus diberi paparan Bahasa Inggris yang baik dan diberikan pelajaran tentang berbagai aspect dari pengujaran Bahasa Inggris. Kata-kata kunci: kelancaran berbicara, kemampuan berbicara, pengajaran bahasa berbasis tugas.